1983 à 1989 : sept ans de réflexion sur l’état et l’histoire de la recherche en communication au Québec - François Yelle (Communiquer)
What is revealed by the reflexive literature on Quebec academic research on media communication in the eighties? That is the research question of this paper, which proposes an analysis of this literature defined as a genre that makes up its own field of study – here, studies in communication – the primary object of reflection. Mobilized by a preoccupation with the interrelations found in the production of scientific knowledge and its environmental context, the research proposes to tease out one of the two regularly occurring themes that cut across the reflexive literature on Communication Studies in Quebec in the eighties: its identity.